TINJAUAN KELENGKAPAN PENGISIAN SURAT KEMATIAN DI RSU BANTEN - Heru Indra Cahya; Erwin Muhtaddin (Journal Of Applied Health Research And Development, 2022)
Background: Filling in the Death Certificate at RSU Banten is the part that gets attention in this study. The Death Certificate form was found to be incomplete in patient identification, completeness of important reports, author authentication and good records. The Medical Certificate of Cause of Death (SMPK) is the main source of mortality data. Death information is usually obtained from health practitioners or in cases of death due to accidents, violence and other diseases. Based on a preliminary study in March 2020 at Banten General Hospital, it was found that out of 20 death certificate forms there were 10 incomplete death certificate forms, including the incomplete identification component of 7.75 (39%) such as in the death serial number section, the main number population and population number. 9 (45%) important report components were incomplete, such as the type of examination, ICD code, method and location of burial. The incomplete authentication component of 10 (50%) is as in the reporting signature and reporting name. An incomplete record component of 6.6 (35%) is like a lot of blanks. The purpose of the study was to find out the Completeness of Filling in Death Certificates at RSU Banten and the results of this study were expected to be useful for hospitals as input and consideration in addressing the issue of completeness of medical certificates causing death. and the approach used in this research is to use a comparative approach, namely through a checklist and interviews at RSU Banten. The research method used is quantitative research. The population in January- February 2020 was 233 death certificate forms at RSU Banten, while the subject population was 12 officers who were responsible for completing death certificates. The sample object taken for this research is a Death Certificate form as many as 77 samples. While the sample of subjects in this study were 2 officers who filled out death certificates. Sampling Technique Subjects in this study used non-random (non-probability sampling) with purposive sampling. The results showed that the SOP (Standard Operating Procedure) already exists and is complete which regulates the Filling of Death Certificates at RSU Banten in the installation section of the funeral procession (IPJ), but it is still not fully implemented because there are still many incomplete forms, from the 5 SOP items it is known that those who are complete with SOP guidelines are (100%) while those that are incomplete with SOP guidelines are (0%). The results of completeness in patient identification with a complete percentage are found in the sub-components of medical record numbers and names, which are 77 (100%), while the incomplete percentages are found in the sub-components of death serial number, population identification number and population identification number, which is 77 (100% , Important reports on death certificates that are filled out completely are found in the time of death sub-component, which is 77 (100%), while the completeness of filling out important reports that are incomplete on the death serial number is 77 (100%).Authentication Author on death certificates which is filled in completely is contained in the sub-components of the doctor's TTD sign and the doctor's name, which is 77 (100%), while the incomplete completeness of author authentication on the reporting blood pressure, the name of the reporter, the identity card number of the reporting person, the address of the reporter is 77 (100%). Both the death certificate that is filled in completely, there are sub-components, there are no scribbles and there is no type - ex, which is 77 (100%). while the completeness of incomplete filling on a good record is found in the sub-components, there are no empty parts, namely 77 (100%). Data collection was carried out by survey, namely the researcher conducted direct interviews with respondents using a questionnaire. The research results obtained the following data; There were 97 toddlers who had pneumonia or 26.5%, almost all of them 94.5% of mothers had good knowledge about pneumonia, 46.7% of mothers had sufficient behavior and 49.5% of mothers had sufficient attitudes and more than half of them 70.2% of mothers had not been exposed to information about pneumonia. The Bivariate results found that attitude and information exposure had a significant relationship with the incidence of pneumonia, while behavior and knowledge had no significant relationship with the incidence of pneumonia among toddlers in the city of Cilegon. From the results of this study, it is hoped that the Cilegon City Health Office can increase socialization and counseling about pneumonia through cooperation with related agencies so that it can improve the degree of public health.